Kombinasi Ekstrak Bawang Merah (Alium ascalonicum) dan Minyak Kayu Putih (Melaleuca cajuputi) terhadap Mortalitas Pediculus humanus capitis: The Effectiveness of Shallot (Allium ascalonicum) Extract and Cajuput Oil (Melaleuca caju - puti) Combination on the Mortality of Pediculus humanus capitis - Faza, Thariqi Mushthafa; Wardani, Dita Pratiwi Kusuma; Hikmawati, Isna; Azizah, Atika Nur; Mujahid, Ikhsan; Almanfaluthi, Muhammad Luthfi; Widodo, Oei Stefani Yuanita (Perkumpulan Entomologi Kesehatan Indonesia, 2025)
Pediculosis is caused by Pediculus humanus capitis and is characterized by scalp itching. The use of chemical pediculicides can cause scalp irritation and toxic hazards. The use of natural ingredients, such as a combination of shallot extract and eucalyptus oil, is used as an alternative pediculicide to reduce the impacts caused by the use of synthetic pediculicides. This research aims to determine the effectiveness of combining shallot extract and eucalyptus oil in eradicating head lice. This research is a true experimental type with a post-test only with control group design consisting of a positive control group (1% permethrin), a negative control (aquadest), and five treatment groups of 5% shallot extract combination and eucalyptus oil in ratios 1:1 (P1), 1:2 (P2), 2:1 (P3), 1:3 (P4), and 3:1 (P5). Data were analyzed using the Friedman test, and LT50 and LC50 were analyzed using probit analysis. There was a difference in the effectiveness of the 5% shallot extract combination and 5% eucalyptus oil. Group P4 was the most effective in causing mortality of Pediculus humanus capitis, with an LC50 value of 0.056% at 30 minutes, while the LT50 value was 0.781 minutes in group P4. The combination of shallot extract and eucalyptus oil in a 1:3 ratio was the most effective alternative to traditional plant-based pediculicides. The combination of shallot extract and eucalyptus oil has the potential to serve as an alternative pediculicide